Light-to-moderate drinking and dementia risk: The former drinkers problem re-visited - Roizen, R.; Fillmore, Kaye; Chikritzhs, Tanya; Stockwell, Tim (Routledge, 2013)
A growing literature ostensibly supports the contention that light-to-moderate drinking offers a protective effect with respect to late-onset dementia. The former drinkers problem, however, may mitigate or even erase any observed protective relationship. Using three recent meta-analyses as windows on the alcohol and dementia literature [Anstey, K.J., Mack, H.A., & Cherbuin, N. (2009). Alcohol consumption as a risk factor for dementia and cognitive decline: Meta-analysis of prospective studies. American Journal of Geriatric Psychiatry, 17, 542–555; Peters, R., Peters, J., Warner, J., Beckett, N., & Bulpitt, C. (2008). Alcohol, dementia and cognitive decline in the elderly: A systematic review. Age Ageing, 37, 505–512; Neafsey, E.J., & Collins, M.A. (2011). Moderate alcohol consumption and cognitive risk. Neuropsychiatric Disease and Treatment, 7, 465–484], we offer a critical review and re-examination of 24 studies employing one or another strategy to control or evaluate the impact of the former drinkers problem on the alcohol and cognitive impairment relationship.Our review is organized around four strategies and problem areas found in these studies, namely: (1) analyses using light drinkers instead of abstainers as reference, (2) time dimension problems attaching to the nondrinker category in analyses, (3) analyses excluding former drinkers or drinkers who changed categories over a study's course, and (4) other approaches and associated problems. Our review suggests that the former drinkers problem has been only incompletely addressed in this still new literature on alcohol's possible protective cognitive effects. As evidenced in the three meta-analyses employed in this review, only a fraction of alcohol and dementia studies addressed the former drinkers problem and, among those, still fewer addressed the problem adequately. Several reasons for this deficiency in the literature are discussed. We conclude that the impact of former drinkers on the alcohol and dementia relationship remains an open question.